2017
DOI: 10.24912/jm.v21i1.146
|View full text |Cite
|
Sign up to set email alerts
|

KOMPETISI DAN STABILITAS PERBANKAN DI INDONESIA Suatu Pendekatan Analisis Panel Vector Autoregression

Abstract: Abstract:Banking fragility phenomenon in the world as well as in Indonesia whip out some interesting issues to be investigated. The objective of this study is to investigate the dynamic causality relationship between competitionand stability of bank in Indonesia. The relationship between competition and stability of bank has long been a controversy before some crises takes place in the world either in theoretical or in empirical sphere. The crucial question such as will competition increase stability of bankin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Khemraj & Pasha (2009) stated GDP with a negative impact, but interest rate, inflation, forex, and excessive lending positively correlate with the increase of NPL and NPF. Apriadi et al (2017) found a negative relationship between NPL and NPF and GDP growth and inflation, but a positive relationship with unemployment. Leka et al (2019) and Donath et al (2014) found that the real GDP growth rate and inflation rate-CPI determined bad loans in the banks from Central and Eastern Europenegatively affect the unemployment rate a positive effect.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Khemraj & Pasha (2009) stated GDP with a negative impact, but interest rate, inflation, forex, and excessive lending positively correlate with the increase of NPL and NPF. Apriadi et al (2017) found a negative relationship between NPL and NPF and GDP growth and inflation, but a positive relationship with unemployment. Leka et al (2019) and Donath et al (2014) found that the real GDP growth rate and inflation rate-CPI determined bad loans in the banks from Central and Eastern Europenegatively affect the unemployment rate a positive effect.…”
Section: Introductionmentioning
confidence: 90%
“…Funding liquidity is considered a critical factor that plays an essential role in bank stability but, at the same time, is a significant determinant of the banking crisis (Hugonnier & Morellec, 2017). The function of banking in the economy is crucial because it controls the fund's distribution from the public (third party) to businesses that require it as one of the leading national economic drivers; thus, the function of banking as intermediation or "heart of the economy" (Apriadi et al, 2017). The development of the Islamic banking industry and financial institutions, both conventional and sharia, follows the corporation's fundamental performance and fluctuations in global, regional, and national economic conditions generally (Santosa, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This condition can generate a risk of loss, which in turn can affect the Bank's stability. This is because they believe in the too big to fail policy that they will explicitly or implicitly be protected by the government safety net (Apriadi et al, 2017). The banking system concentrated in a few large banks can threaten the risk of failure and cause losses involving many depositors.…”
Section: Introductionmentioning
confidence: 99%